Analisis Nilai Pendidikan Karakter dalam Buku Cerita Rakyat “Danau Toba dan Pulau Samosir” - Rahmatullah, Alif; Permata, Deya Putri; Jamilah, Nur; Masodi, Masodi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to examine the value of character education in the folklore book “Lake Toba and Samosir Island”. Character education is an important aspect to form the next generation of an advanced and noble nation, this research uses a method, namely qualitative research methods with a literature study approach. Data sources were obtained from the folklore book “Lake Toba and Samosir Island”. The data analysis technique carried out in this study is to reread the data, and analyze the character education values in it. The results showed that there are many character education values in the folklore book “Lake Toba and Samosir Island” which is very suitable to be read by elementary school students. There are 18 values of character education as mentioned by Kemendiknas, namely: Religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the country, respect for achievement, friendly/communicative, peace-loving, fond of reading, environmental care, social care. Based on this research, the results found in the analysis of character education values in the folklore book “Lake Toba and Samosir Island” are the values of religion, honesty,  hard work,  independence  friendly/communicative, social care, responsibility.